Traditional Chinese medicine in the management of diabetic foot ulcers: an overview of meta-analyses - Xiong, Xiaocui; Liu, Xiaoman; Wan, Siyuan (Frontiers in Medicine, 2025)
BackgroundThe global rise in diabetic foot ulcer (DFU) complications necessitates more effective therapeutic strategies. Traditional Chinese Medicine (TCM) has been increasingly explored as a potential adjunctive therapy for DFU management. This umbrella review synthesizes evidence from meta-analyses to evaluate the effectiveness and safety of TCM interventions.MethodsA systematic search of PubMed, Scopus, and Web of Science was conducted through May 2025. Eligible meta-analyses were selected based on predefined criteria, and methodological quality was appraised using the AMSTAR 2 tool.ResultsEleven meta-analyses, encompassing 44 datasets and reporting pooled effect sizes for seven clinical outcomes, were included. The TCM interventions analyzed were both topical and oral. The findings revealed that TCM significantly improved DFU-related outcomes, including ulcer size reduction, shortened healing time (by up to 5.7 days in some trials), increased cure rates (up to a 43% relative improvement), and enhanced overall treatment effectiveness. Notably, longer intervention durations and larger sample sizes were associated with stronger positive effects.ConclusionThis review underscores the therapeutic potential of TCM, particularly topical formulations, in enhancing clinical outcomes and accelerating recovery in patients with diabetic foot ulcers.